Partisipasi Masyarakat Dalam Pencegahan Dan Pengendalian Kebakaran Lahan Gambut Di Hutan Lindung Gambut (Hlg) Londerang Provinsi Jambi - Rosyani; zainuddin; Bambang Hariyadi (Jurnal Pembangunan Berkelanjutan, 2019)
This study aims to analyze the level of community participation and the relationship of between community knowledge with participation in the fire prevention and suppression from peat in Londerang Peat Protection Forest (HLG), Jambi Province. Research uses a mixed method by combining quantitative and qualitative research. The qualitative data sampling uses purposive sampling by collecting data through in-depth interviews. The analytical method used is quantitative descriptive analysis method supported by qualitative and cross tabulation methods. For the analysis of the association relationship using the Spearman Rank correlation formula method with respondents (n) <30. To analyze the comparison of the level of knowledge and community participation, the t-test was performed using the independent t-test. Based on data analysis, it is known that the level of participation for the community of Rawasari Village is at the level of partnership, while the level of participation of Manis Mato villagers is at the level of informing. The level of knowledge and level of community participation in Rawasari Village is higher than the knowledge of the Manis Mato Village community. The relationship of knowledge to community participation in Rawasari and Manis Mato Villages has a very strong correlation coefficient, rsrawasari = 0,9877 and rsmanismato = 0,9895. Correlation value rs (Spearman Rank correlation coefficient) shows that there is a very significant effect (α = 0.01) between knowledge of the level of community participation in the prevention and control of peatland fires in Londerang Peat Protection Forest (HLG). The strategy to increase and strengthen knowledge and community participation in both villages can be done through assistance to increase knowledge through socialization and community participation through training and improvement of supporting facilities and technical knowledge on the use of various facilities needed in the form of community empowerment to increase knowledge and participation in prevention and control fire peat fires in Londerang Peat Protection Forest (HLG).